Increased serum levels of quinolinic acid indicate enhanced severity of hepatic dysfunction in patients with liver cirrhosis - Lahdou, Imad; Sadeghi, Mahmoud; Oweira, Hani; Fusch, Gerhard; Daniel, Volker; Mehrabi, Arianeb; Jung, Gregor Eric; Elhadedy, Hazem; Schmidt, Jan; Şandra-Petrescu, Flavius Ionuţ; Iancu, Mircea; Opelz, Gerhard; et al. (Human immunology, 2013)
Background: The Model for End-Stage Liver Disease (MELD) score is a tool for assessment of the degree of hepatic insufficiency/failure. Quinolinic acid (QuinA) is a tryptophan metabolite produced by activated macrophages. Here we investigate whether the degree of systemic inflammation (QuinA, neopterin, CRP and IL-6) correlates with clinical liver dysfunction according to the MELD Score. Method: Ninety-four patients with liver cirrhosis were categorized into 2 groups according to baseline MELD score (group I, MELD <20, n=61, and group II, MELD ⩾20, n=33). Results: Serum levels of QuinA, neopterin, CRP, and IL-6 significantly correlated with MELD score (r=0.77, 0.75, 0.57, and 0.50; p<0.0001, respectively). Patients of group II had significantly higher serum levels of QuinA, neopterin, CRP, and IL-6 than group I (p⩽0.0001). ROC curve analysis showed that QuinA and neopterin are more sensitive markers for severity of liver disease than established markers of inflammation such as CRP and IL-6 (sensitivity=86% and 79%, respectively) (AUC=0.89 and 0.89, respectively). QuinA provided the most sensitive index with regard to the identification of patients with hepatic encephalopathy. Conclusion: Serum levels of QuinA reflect the degree of liver dysfunction. Moreover, high levels of QuinA may serve as a sensitive indicator of hepatic encephalopathy.